2009
DOI: 10.1136/sti.2008.034009
|View full text |Cite
|
Sign up to set email alerts
|

Trends in age at first sex in Uganda: evidence from Demographic and Health Survey data and longitudinal cohorts in Masaka and Rakai

Abstract: Objectives:To derive the best possible estimates of trends in age at first sex (AFS) among successive cohorts of Ugandan men and women based on all the data available from the Demographic and Health Surveys (DHS) and cohort studies in Masaka and Rakai districts.Methods:The datasets from the DHS, Masaka cohort and Rakai cohort were analysed separately. Survival analysis methods were used to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
7
28
0
Order By: Relevance
“…Increased HIV awareness and knowledge of preventive behaviors may in part be responsible for this modest shift away from premarital sexual activity, although further analysis is needed to draw such a conclusion. Similar patterns have been observed in Kenya and Ghana (Zaba et al, 2004), and in Uganda, where the youngest cohort of women had a lower rate of premarital intercourse compared to earlier cohorts despite a delay in the age of marriage (Mensch et al, 2006, Slaymaker et al, 2009, Zaba et al, 2004). In a study of DHS data from southern and eastern Africa, Harwood-Lejeune also found that adolescent pre-marital sexual activity was declining (Harwood-Lejeune, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Increased HIV awareness and knowledge of preventive behaviors may in part be responsible for this modest shift away from premarital sexual activity, although further analysis is needed to draw such a conclusion. Similar patterns have been observed in Kenya and Ghana (Zaba et al, 2004), and in Uganda, where the youngest cohort of women had a lower rate of premarital intercourse compared to earlier cohorts despite a delay in the age of marriage (Mensch et al, 2006, Slaymaker et al, 2009, Zaba et al, 2004). In a study of DHS data from southern and eastern Africa, Harwood-Lejeune also found that adolescent pre-marital sexual activity was declining (Harwood-Lejeune, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…The median age at first sex for women is about 5 years younger than for men in Uganda and Umkhanyakude. 23 24 However, by the age of 25 years, over 90% of both men and women reported having a sexual partner during the past 12 months and can be said to be sexually active. In older women (>40 years), a decline in the proportion that is sexually active was observed in all sites.…”
Section: Discussionmentioning
confidence: 99%
“…Kyamulibwa, run by the UK Medical Research Council/Uganda Virus Research Institute, is located within Kalungu District and began collecting demographic and health data on the population in 1989 [12]. Rakai, run by the Rakai Health Sciences Program, is located within Rakai District and began its open-community cohort for 15–49 year olds in 1994 [12]. Background characteristics of the two sites are displayed in Table 1.…”
Section: Methodsmentioning
confidence: 99%